Representasi Identitas Perempuan dalam Ranah Domestik– Sebuah Kajian Semiotika Budaya pada Peribahasa Sunda - Farieda Ilhami Zulaikha (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
Proverbs are an identity marker for the language users in one region. The uniqueness and cultural diversity can be seen from the interpretation of the proverb. Therefore, this study aims to examine women's identity in the domestic domain in Sundanese proverbs. This research involves semiotic and cultural analysis. The stages of analysis are divided into 3 coding, classification, and analysis. This research is formulated to answer two issues; 1) signs found in Sundanese proverbs including symbols, indices and icons in representing the role of women in the domestic sphere in Sundanese society, and 2) interpretations of signs associated with cultural concepts. Based on the analysis the results are 1) women’s sign in Sundanese proverbs are related to kitchen, bed, and cosmetic, 2) Those three signs for women construct women’s position in domestics sphere. Women are binded to be in the kitchen and has no power on their own body.